Oral Health, Nutritional Choices, and Dental Fear and Anxiety - Jennifer R. Beaudette; Peter C. Fritz; Philip J. Sullivan; Wendy E. Ward (MDPI AG, 2017)
Oral health is an integral part of overall health. Poor oral health can lead to an increased risk of chronic diseases including diabetes mellitus, cardiovascular disease, and some types of cancer. The etiology of these diseases could be linked to the individual's inability to eat a healthy diet when their dentition is compromised. While periodontal or implant surgery may be necessary to reconstruct tissue around natural teeth or replace missing teeth, respectively, some individuals avoid such interventions because of their associated fear and anxiety. Thus, while the relationship between poor oral health, compromised nutritional choices and fear and anxiety regarding periodontal procedures is not entirely new, this review provides an up-to-date summary of literature addressing aspects of this complex relationship. This review also identifies potential strategies for clinicians to help their patients overcome their fear and anxiety associated with dental treatment, and allow them to seek the care they need.